Recurrent Respiratory Papillomatosis (Springer International Publishing, 2018)
This volume provides a comprehensive review of recurrent respiratory papillomatosis and an up-to-date understanding of the etiology, pathophysiology, and management of these rare tumors caused by the human papillomavirus (HPV). The text covers the potential role of vaccines, its significant role in prevention and the controversy surrounding the use of them. Topics such as impact, quality of life, and patient advocacy are also covered and are vital to understanding the disease from the patient perspective. Recurrent Respiratory Papillomatosis will be an invaluable resource for practicing otolaryngologists, laryngologists, anesthesiologists, infectious disease specialists, and residents participating in the care of patients with this disease. .